2016
DOI: 10.1016/j.adolescence.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Being targeted: Young women's experience of being identified for a teenage pregnancy prevention programme

Abstract: Research on the unintended consequences of targeting 'high-risk' young people for health interventions is limited. Using qualitative data from an evaluation of the Teens & Toddlers Pregnancy Prevention programme, we explored how young women experienced being identified as at risk for teenage pregnancy to understand the processes via which unintended consequences may occur. Schools' lack of transparency regarding the targeting strategy and criteria led to feelings of confusion and mistrust among some young wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…A tabulated outcomes summary for 36 studies is presented in Appendix B. A few studies (n ¼ 7) were excluded because rather than looking into the effect or outcome of the program, they looked into the reaction of participants being selected (Sorhaindo et al, 2016) or described the service provided (Bigson et al, 2020;de Vries et al, 2016). Other studies focused on personnel providing the service (Raible et al, 2017), explored the problems facing adolescents (Høie et al, 2017), or uncovered barriers that prevented the initiation of a program designed for tween children (Marttinen et al, 2020).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…A tabulated outcomes summary for 36 studies is presented in Appendix B. A few studies (n ¼ 7) were excluded because rather than looking into the effect or outcome of the program, they looked into the reaction of participants being selected (Sorhaindo et al, 2016) or described the service provided (Bigson et al, 2020;de Vries et al, 2016). Other studies focused on personnel providing the service (Raible et al, 2017), explored the problems facing adolescents (Høie et al, 2017), or uncovered barriers that prevented the initiation of a program designed for tween children (Marttinen et al, 2020).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…One study, identified by the snowball method, was conducted in South Korea (Lee and An, 2016) and described a randomized experiment testing the effects of messages about the controllability of a condition (i.e., individual responsibility for the onset of a condition) and group categorization on perceived stigma. The other study, conducted in the United Kingdom, reported results of interviews conducted to learn about the unintended consequences of an intervention targeting a high-risk group (Sorhaindo et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Messages need to balance the potential benefits of presenting health disparities information to raise awareness and promote behavior change with the potential harms, such as stereotyping and stigmatization (Institute of Medicine, 2002; Guttman and Salmon, 2004;Coleman and Hatley Major, 2014;Keller et al, 2014). For example, while targeting is used to increase the relevance of messages to a priority audience, presenting information that links a particular high-risk group with a negative health condition (i.e., highlighting health disparities) can stigmatize the priority audience (Guttman and Salmon, 2004;Friedman et al's, 2014) and cause them to perceive messages as reinforcing stereotypes (Sorhaindo et al, 2016). Next, we discuss literature addressing our second RQ on the potential unintended adverse effects of communicating about health disparities, including stigmatization and stereotyping, victim blaming, negative emotional reactions, mistrust of health information, and boomerang effects.…”
Section: Potential Unintended Adverse Effects Of Messages Communicatimentioning
confidence: 99%
“… 13 Targeted interventions may also face difficulties in identifying and recruiting such groups, create barriers to engagement through stigmatisation of potential participants 14 and generate iatrogenic effects through reinforcement and normalisation of harmful norms. 15 16 Targeted interventions, which bring together families with high levels of need, may also present problems in relation to feasibility of delivering activities with fidelity. 17 A distinctive aspect of this trial is that the intervention was implemented using a proportionate universal (PU) approach—combining universal provision but with its intensity/scale varied according to need.…”
Section: Introductionmentioning
confidence: 99%